2020
DOI: 10.1111/myc.13213
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pulmonary aspergillosis in the COVID‐19 era: An expected new entity

Abstract: Objectives Information on the recently COVID‐19‐associated pulmonary aspergillosis (CAPA) entity is scarce. We describe eight CAPA patients, compare them to colonised ICU patients with coronavirus disease 2019 (COVID‐19), and review the published literature from Western countries. Methods Prospective study (March to May, 2020) that included all COVID‐19 patients admitted to a tertiary hospital. Modified AspICU and European Organization for Research and Treatment of Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(198 citation statements)
references
References 42 publications
9
173
2
4
Order By: Relevance
“…Decline in cell-mediated immunity has been observed in symptomatic patients, including leukopenia, lymphopenia, and T-cell dysregulation [ 6 ]. In addition, the usage of corticosteroids in the treatment of COVID-19 may further predispose to these fungal infections [ [6] , [7] , [8] , [9] ]. Failure to recognize and treat these infectious complications of COVID-19 will likely lead to higher mortality, which has been described [ [7] , [8] , [9] , [10] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decline in cell-mediated immunity has been observed in symptomatic patients, including leukopenia, lymphopenia, and T-cell dysregulation [ 6 ]. In addition, the usage of corticosteroids in the treatment of COVID-19 may further predispose to these fungal infections [ [6] , [7] , [8] , [9] ]. Failure to recognize and treat these infectious complications of COVID-19 will likely lead to higher mortality, which has been described [ [7] , [8] , [9] , [10] ].…”
Section: Discussionmentioning
confidence: 99%
“…Both infections have been recognized as secondary complications of coronavirus disease 2019 (COVID-19), especially among critically ill patients in the intensive care unit (ICU) [ [6] , [7] , [8] ]. Reports have shown that up to 35% of these patients have invasive pulmonary aspergillosis, which has been associated with prior corticosteroid usage and has led to higher mortality [ [6] , [7] , [8] , [9] ]. In contrast, the incidence of invasive pulmonary mucormycosis following COVID-19 is rare, with only two cases currently reported [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, laboratory features that are typically abnormal in patients suffering from severe COVID-19 include elevated D-Dimer levels, ferritin, and Interleukin (IL)-6 levels, elevated cardiac biomarkers, and hepatic enzymes [ 11 , 77 , 80 , 81 ]. In cases where bacterial superinfection is suspected, procalcitonin might be helpful in addition to microbiological sampling, bronchoalveolar lavage, and galactomannan testing for fungal infection/aspergillosis [ 82 , 83 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Reasons for the increased susceptibility to secondary infections are not yet fully understood, but it is speculated that respiratory stress, a dysregulated immune response, and the use of immunosuppressive drugs (e.g., steroids) may play a role [ 156 ]. The latter might also be responsible for an increased incidence of invasive pulmonary aspergillosis in patients with CARDS [ 83 ]. In patients with superinfections, a careful antibiotic/anti-mycotic stewardship should be applied [ 156 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Since antagonistic TLR and NLR interactions tend to be initiated over time measured by many hours or several days (see Section 2.3), Figure 8 may well explain how the cytokine storm in severe COVID-19 is initiated and Figure 3A the status of the innate system as it attempts to moderate its cytokine production. One final complication is that many severe COVID-19 patients are treated with multiple antibiotics [201][202][203][204][205][206][207][208][209][210][211][212], which may further modify the expression of bacterially activated TLR and NOD1/NOD2.…”
Section: Do Combinations Of Viruses and Bacteria Explain Innate Recepmentioning
confidence: 99%